Catalytic activity of Cu-ZSM-5 and HZSM-5 zeolite for single step conversion of methane to liquid hydrocarbon - Saidina Amin, Nor Aishah; Anggoro, Didi Dwi; Zakaria, Zaki Yamani; Prasetyoko, Didik; Tan, Eng Fong; Law, Kian Meng; Esam, Azwan (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The economical conversion of methane(CH4), the principal component of natural gas, to liquid fuels, particularly gasoline (C5-H10) is one of the main challenges in the gas to liquids (GTL) technology. The existing technology based on Fischer-Tropsch synthesis is adapted by SASOL in South Africa and SMDS in Malaysia.However, the process is energy intensified and costly. The research for the catalyst that is highly active to convert methane to higher hydrocarbons directly has mainly focused on microporous material such as the ZSM-5. The HZSM-5 and Cu-ZSM-5 zeolites were synthesized by hydrothermal crystallization at 170C for seven days from mixtures containing sodium silicate, aluminium sulfate and tetrapropylammonium bromide (copper nitrate is added for the synthesis of Cu-ZSM-5). The catalysts were characterized using X-Ray Diffraction (XRD),Temperature-Programmed Desorption (TPD) and Nitrogen Adsorption. Methane with 99.9% purity was reacted with compressed air at atmospheric pressure and temperature, T=800C. The performance of synthesized HZSM-5 and and Cu-ZSM-5 was testes in a fixed-bed micro reactor at Weight Hour Space Velocity (WHSV) of 10440 ml.g(-1).hr(-1) with CH4/O2 ratio=10:1. The percentage of SiO2 and Al2O3 in the zeolite gel affected the surface area, micropore area, pore size and micropore volume as well as the acidity of zeolite samples. While the conversion of methane decreased as a result of loading the Cu ions, the selectivities in the gasoline range hydrocarbons exhibit a considerable improvement over catalyst with moderate to high acidity range. For a catalyst with a weak acidity, loading metal ions into the frame work may retard the formation of C5-10 hydrocarbons.